Cervical cancer screening : safety, acceptability, and feasibility of a single-visit approach in Bulawayo, Zimbabwe - Fallala, Muriel Selma (Stellenbosch : Stellenbosch University, 2015)
Thesis (MFamMed)--Stellenbosch University, 2014.